Gambaran Waktu Tunggu Pelayanan Resep Di Puskesmas Kasongan 2 Kecamatan Katingan Hilir - Rivandha, Junia Angelina; Ardhany, Syahrida Dian (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
AbstractPatient waiting time when picking up a prescription at a health center is one element that can affect satisfaction. Waiting time for pharmacy services is the duration required to obtain medication from the time the prescription is received until the medication is given by the pharmacy team. Long waiting times are an issue that often arises and results in patient dissatisfaction in a number of health centers. The study aims to see the average time required for pharmacy services related to non-compound and compounded drug prescription services at the Kasongan 2 Health Center, Katingan Hilir District. This study uses a descriptive method with a quantitative approach. Purposive Sampling is a sampling technique used in this study. The data generated were 429 sample prescriptions, there were 62 non-compound prescriptions and 367 compounded prescriptions. The time considered optimal and in accordance with the standard (Minister of Health Decree) is when non-compound drug services are completed in ≤30 minutes while compounded drugs are completed in ≤60 minutes. However, based on the service standards at Kasongan 2 Health Center, the ideal time for service is ≤30 minutes for non-compound drug prescriptions and compounded drugs are ≤40 minutes. The research data obtained showed that the average waiting time for non-compound drug prescription services was 6.43 minutes, while for compounded drugs it was 16.9 minutes. From these results, it was concluded that at Kasongan 2 Health Center in terms of waiting time for drug prescriptions served by the pharmacy that the established standards were met, both according to the the service standards at Kasongan 2 Health Center and 2008 Minister of Health Decree.